Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species - Sepúlveda, Tatiana A.; Souza, Diego de S.; Echeverry, Angela; Marinoni, Luciane; Carvalho, Claudio J.B. de (European Journal of Taxonomy, 2020)
The genus Teloneria Aczél, 1954 is resurrected from synonymy with Chaetonerius Hendel, 1913 to include four species: Teloneria apicata (Edwards, 1919) comb. nov., Teloneria bimaculata (Edwards, 1919) comb. nov., Teloneria juceliae Sepúlveda & Souza sp. nov. and Teloneria ladyae Sepúlveda & Souza sp. nov. Lectotypes for Telostylus apicatus Edwards, 1919 and its junior synonym, Telostylinus apicalis Enderlein, 1922, and for Telostylinus ornatipennis Enderlein, 1922, junior synonym of Teloneria bimaculata comb. nov., are designated. An identification key to Chaetonerius, Telostylus Bigot, 1859 and Teloneria, with emphasis on the identification of the species of Teloneria, illustrations and distribution data are provided.